Platelet-to-Lymphocyte Ratio and CA125 Level as a Combined Biomarker for Diagnosing Endometriosis and Predicting Pelvic Adhesion Severity - Guo, Cuishan; Zhang, Chiyuan (Frontiers in Oncology, 2022)
Adhesion is a significant biological characteristic of endometriosis, and accurate evaluation of the pelvic adhesion is necessary for surgical treatment. Serum CA125 is yet the most common used biomarker in the diagnosis and follow-up of patients with endometriosis despite of its high false-positive rate and low specificity. Herein, we aimed to examine the diagnostic value of the combination of the platelet-to-lymphocyte ratio (PLR) and CA125 for patients with different stages of endometriosis and their correlations with pelvic adhesion. We retrospectively analyzed the clinical data and blood count parameters of patients with both endometriosis and other benign ovarian tumors. The mean level of CA125, the PLR and the combined marker (CA125 plus PLR) in the EMs group were significantly higher than those in the Cyst group (P < 0.05). ROC curve analysis was used to compare the diagnostic values of serum PLR, CA125, and the combined marker in ovarian endometriosis. The cut-off value of the PLR was 176.835, with 28.3% sensitivity and 96.9% specificity. The cut-off value of CA125 was 31.67 U/mL, with 84.1% sensitivity and 87.4% specificity. The cut-off value of the combined marker was 3894.97, with 83.4% sensitivity and 95.8% specificity. It was found that the severity of adhesion in endometriosis was positively correlated with the PLR (r = 0.286, P < 0.01), CA125 (r = 0.276, P < 0.01), and combined marker (r = 0.369, P < 0.01). The combined marker showed the highest AUC value (0.751, 95% CI: 0.666–0.837), with a sensitivity of 56.0% and a specificity of 89.6%, and the cut-off value was 9056.94. Besides, the levels of CA125, PLR, and their combination were significantly elevated in patients with endometriosis. The combined marker was not only positively correlated with pelvic adhesion but also showed a greater diagnostic value and specificity than CA125 alone. These findings indicate that the combined marker may be a potential inflammatory biomarker playing an important role in the diagnosis and assessment of adhesion in endometriosis.